Life-Threatening Cyanide Intoxication after Ingestion of Amygdalin in Prehospital Care. (4th May 2022) - Cmorej, Patrik; Bruthans, Petr; Halamka, Jaroslav; Voriskova, Irena; Peran, David
Abstract: Amygdalin is originally a natural cyanogenic glycoside available as a dietary supplement used in the alternative treatment of cancer patients. Amygdalin hydroxylates to toxic cyanide in the body, which can cause life-threatening intoxication. The case report presents a 72-year-old patient with life-threatening cyanide poisoning after ingesting a dietary supplement containing amygdalin identified in prehospital care, which was successfully treated with hydroxocobalamin.